Verbs of Thought as a Way of Characterizing Hero-Intellectual in Short Prose of A. P. Chekhov and A. I. Kuprin - M. A. Dubova; V. A. Tamazyan (Научный диалог, 2022)
The verbs of thought and their role in the characterization of the linguistic personality of the hero-intellectual based on the stories of A. P. Chekhov “My Life” and A. I. Kuprin “Moloch” is examined in the article. It is noted that this study will allow a comparative analysis of the characters in order to identify the typical and individual in their ideas about the world, in the system of their views on the world, in the direction of their thought process. The relevance of the work is determined by addressing the problem of describing a linguistic personality in a literary text. The novelty of the article lies in the study of variations in the representation of the model personality of the hero-intellectual in late 19th century Russian prose. The article uses methods of semantic and linguo-stylistic analysis, comparison and description of language units. The conclusions substantiate that in the presence of distinctive features in the mental activity of the characters, as well as in the principles of constructing their speech strategies, there are common, typological properties, which is due to their belonging to the same social stratum and cultural and historical era. The authors believe that these characters can be attributed to the model language personality of a Russian intellectual at the turn of the 19th—20th centuries.